The empirical review on the working environment, motivation and social factors and the career performance in Oman / Salim Al Abdali and Abul Bashar Bhuiyan - Al Abdali, Salim; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
A strategically effective, hygienic, and healthy environment ensures bringing satisfaction among the employees while a drab, challenging, and competitive atmosphere leaves a seriously poor impact on the employees. At different times, employees are required to face a number of challenges, both operational and organizations where they are essentially expected to invest their best knowledge, skills, and experience, However, in a poorly developed atmosphere an employee basically refuses to invest his or her abilities which ultimately creates challenges for the organization. Therefore, the aim of the present study is to evaluate the effects of the working environment, motivation and social factors on career performance in Oman. The study used online empirical recourses by the name of working environment, motivation and social factors and career performance in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCOHOST, etc. The findings summarized that maintaining a sophistically impressive working environment basically helps an organization to maintain a good image before the pool of skilled candidates in the market and helping it to acquire the best talents. Moreover, the study also concluded that the majority of the organizations across the globe are focusing on maintaining an effective working atmosphere to keep the employees more engaged to the organization than that of the other and it has a significant role in the comprehensive development of the organization. The findings of the study draw a guideline for future scope of empirical in depth study in the area of the career performance in Oman and the regions.